Cell failure mechanisms in PEM water electrolyzers - Millet, P.; Ranjbari, A.; de Guglielmo, F.; Grigoriev, S.A.; Auprêtre, F. (International journal of hydrogen energy, 2012)
PEM water electrolysis offers an efficient and flexible way to produce “green-hydrogen” from renewable (intermittent) energy sources. Most research papers published in the open literature on the subject are addressing performances issues and to date, very few information is available concerning the mechanisms of performance degradation and the associated consequences. Results reported in this communication have been used to analyze the failure mechanisms of PEM water electrolysis cells which can ultimately lead to the destruction of the electrolyzer. A two-step process involving firstly the local perforation of the solid polymer electrolyte followed secondly by the catalytic recombination of hydrogen and oxygen stored in the electrolysis compartments has been evidenced. The conditions leading to the onset of such mechanism are discussed and some preventive measures are proposed to avoid accidents. ► Hydrogen production by PEM water electrolysis. ► Investigation of cell failure mechanisms and discussion on safety issues. ► Conditions for membrane perforation at elevated current densities. ► Hydrogen–oxygen combustion and irreversible electrolysis stack degradation.